Wicksell, Keynes, and the New Neoclassical Synthesis: What Can We Learn for Monetary Policy?. (July 2014) - Tamborini, Roberto; Trautwein, Hans‐Michael; Mazzocchi, Ronny
<x xml:space="preserve">Abstract</x> The New Neoclassical Synthesis (NNS) provides the established macroeconomic foundation for monetary policy. The Great Recession has, however, unveiled a number of unresolved issues. Prominent scholars have stressed the connections of the NNS with the founders of macroeconomic thought, Wicksell and Keynes. Our main contention is that the NNS fails to consider, and learn from, the hallmark of Wicksell's and Keynes's approaches to business cycles, namely investment–saving imbalances (ISI). Systematic studies of macroeconomic instability, and notably the Great Recession, give prominence to this phenomenon. Drawing on Wicksell's and Keynes's insights, this paper provides a framework to deal with ISI and monetary policy according to modern theoretical standards and techniques (e.g. agents seek to optimize intertemporally and markets clear). Section 2 of the paper clarifies some basic theoretical issues underlying the NNS vis‐à‐vis Wicksell and Keynes. Section 3 presents a dynamic model whereby it is possible to assess some basic issues concerning the macroeconomics of ISI that are at variance with the NNS. Section 4 shows how system stabilization can be achieved by means of a 'Wicksellian' interest‐rate rule, which, however, displays dynamic features and conditions that differ from the current NNS consensus. Central banks may thus learn that ISI deserve careful symptom monitoring, and that they require greater attention to the dynamic stability of choices of policy reaction functions.